PENGEMBANGAN E-MODUL AKTIVITAS FISIK UNTUK PENCEGAHAN DIABETES MELITUS REMAJA BAGI GURU DI SMPN 18 BANDUNG - Larasati Eka Putri; Ridwan Setiawan (Politeknik Kesehatan Kemenkes Bandung, 2025)
The prevalence of juvenile diabetes mellitus (DM) in Bandung increased sharply from 9 cases in 2021 to 53 cases in 2022. Contributing factors include low health education awareness and the inactivity of 65% of adolescents. To address this, an e-module was developed for teachers at SMPN 18 Bandung, a school with students at high risk of DM due to hereditary factors and obesity. This study aimed to develop a physical activity e-module for teachers at SMP Negeri 18 Bandung to prevent adolescent DM, utilizing the ADDIE model. This research employed a Research and Development (R&D) methodology utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study involved a sample of 31 homeroom teachers from SMPN 18 Bandung City, with collected data being analyzed using both qualitative and quantitative methods. The ADDIE-based e-module was rated